Can digital financial inclusion help reduce migrant workers’ overwork? Evidence from China - Zhang, Yuzheng; Li, Yundong; Zhuang, Xugao; Liu, Huan; Xu, Yang; Zhang, Shuxian; Yan, Yueping; Li, Yalin (Frontiers in Public Health, 2024)
Migrant workers in China are migrants from the rural to the urban areas who usually work in the cities and return to the countryside after a certain period. Due to China's strict household registration system, they differ significantly from urban residents' access to public services. However, at the same time, China's workers are facing a severe phenomenon of overwork, and the group of migrant workers is even more hard-hit by overwork, which will cause various adverse effects on workers and society and should attract the attention of all sectors of society. This paper focuses on the impact of digital financial inclusion on the overwork of migrant workers. This study considered cross-sectional data containing 98,047 samples based on the 2017 China Migrants Dynamic Survey 2017 (CMDS) and China Municipal Statistical Yearbook. After robustness tests and heterogeneity analysis using probit models, the study found that (1) digital financial inclusion can effectively alleviate overwork among migrant workers; (2) the impact of digital finance on overwork is more significant for the new generation, digitized industries, and self-employed migrant workers; it is also more significant for the South, East, and small and medium-sized cities than for the North, the Midwest, and large cities; (3) job quality and income are crucial factors in how digital financial inclusion affects overwork among migrant workers. Digital financial inclusion can improve the quality of employment for migrant workers and alleviate overwork. However, the income substitution effect partially reduces the inhibitory impact of digital financial inclusion on overwork.